Identification of constraints on rice yield in selected areas of Thailand - Acharee Sattarasart; Suthad setboonsarng; Upasena, Selawa H.; Sornthep Tumwasorn; The united Kingdom (Bangkok : Asian Institute of Technology, 1992)
In this study, the information from the secondary data, farmers and scientists were integrated and analyzed to create a priority ranking of each research option for rice research. The damage areas due to each problem as recorded by extension officers, were used to identify the output loss caused by each source of damage. Farmers were interviewed to identify their problems and their needs. Scientists were interviewed to determine their view of the problems in rice cultivation and the possible options for solutions of each problem. Three different rice ecosystems were investigated: irrigated, rainfed and deepwater rice. For the farm survey, three study areas were investigated: Suphan Buri, Buri Ram and Prachin Buri province for irrigated, rainfed and deepwater rice ecosystem. The results indicate that the major problems in terms of output loss for irrigated rice in rank order from most to less severe are brown planthopper/ragged stunt virus, stem borer, rats, green leafhopper and rice caseworm. The major problems for rainfed rice are drought, brown planthopper/ragged stunt virus, soil problems, stem borer and blast. The major problems for deepwater rice are drought, brown planthopper /ragged stunt virus, submergence, soil problems and weeds. There are differences among the views of rice farmers themselves, the extension officers and the scientists as to the problems facing rice farmers. After accounting for the research cost and the cost for the farmer, the net present value of the net benefit stream was calculated. The net present value analysis indicates that the highest uet present value research activity is the drought for rainfed rice, weeds for irrigated rice and blast for deepwater rice. In the top twenty ranking of research activities for the three rice ecosystems, there are 11 and 9 research activities for rainfed and irrigated ri.ce, respectively . The research activities for deepwater rice are the lowest group because of its small cultivated area. In the top ten ranking of net present value, the research activity on rats, rice caseworm and cutworm for irrigated rice, brown planthopper for rainfed rice and ragged stunt virus for deepwater rice are not regarded as a problem by scientists. The results suggest that scientists may not cover all of farmer problems in rice cultivation and the farmer may be less knowledgeable about the problems of diseases. Each source of information has its strength and weakness. A systemic approach is needed to combine all .sources of information, in order to get the best information.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of science, School of Environment, Resources and Development
Thesis (M.Sc.) - Asian Institute of Technology, 1992
Keywords: Rice -- Research -- Thailand